Prometni ’infarkt’ u gradovima: pokušaji rješenja - Golubić, Jasna (Promet - Traffic&Transportation, 2012)
This paper deals with an attempt at resolving the problem of gridlock in urban areas with particular reference to environment- friendly traffic system. In order to help creating an environment-friendly traffic system, it shall be necessary to take the following measures: gradual relocation of motor traffic by means of a correctly aspected traffic/urban planning policy, rerouting of motor traffic for purposes of improvement of the quality of non- Promet, vol. 6, 1994, br. 5, 127-131 -motorist traffic, improvement of the very method of operation of motor vehicles by technology/control measures and implementation of measures of traffic abatement in residential areas.